Tata Kelola Perusahaan dan Transaksi Pihak Berelasi Terhadap Manipulasi Laba - Arna Suryani; Sespi Jumaida (Universitas Batanghari Jambi, 2021)
Earnings manipulation is an interesting phenomenon to study where corporate governance (GCG) can reduce management behavior that is opertunistic in manipulating earnings and through related transactions can motivate companies to make profits. LQ45 companies for the 2016-2019 period listed on the Indonesia Stock Exchange become this object. Samples were selected based on certain criteria so as many 20 sample companies. This study is a descriptive study with multiple linear regression analysis tools performed classical assumption test and hypothesis testing. The results of the study confirm that companies that implement good corporate governance have good governance and can suppress opportunistic behavior. Related party transactions show that it is not directly proportional to the practice of profit. Companies can reduce opportunistic management by implementing good governance and obtaining more information about relationships in making investment decisions.